SHEAR STRENGTHENING OF REINFORCED CONCRETE BEAM USING EXTERNALLY STRIRRUPS - Arga Saputra; Sri Murni Dewi; Lilya Susanti (Jurnal Rekayasa Sipil dan Lingkungan, 2019)
Initial design errors, especially the installation of stirrups, one of them can cause the beam having shear failure due to installing capacity of stirrups less than the shear capacity that occurs. Shear strengthening in this study used externally stirrups ∅6-75 which were installed in the shear area only. The results of calculation analysis, shear capacity can increase up to 137.82%; 133.42% and 137.12% while the test results increased by 31.58%; 0% and 4.76% in this caseload did not look significant from the results of calculation analysis. However, when viewed from crack pattern that occurs without external stirrups, outer ring has a combination of flexural and shear cracks occurs quite much, besides of flexural and shear cracks, combination of crack also occurs because of pressure beam reach pressure capacity first rather than tensile beam because the ratio of installed reinforcement is over reinforced. Meanwhile, in the beam with external stirrups, the crack pattern that occurs is also a combination of bending and shear cracks, but the cracks that occur are relatively less than the beam without external stirrups. When viewed from the deflection that occurred during the first crack, the reinforced beam experienced a relatively smaller deflection of 0.61 mm beam; 0.31 mm and 0.18 mm rather than beams without externally stirrups 1.28 mm; 0.55 mm and 0.32 mm, so that the beam with external stirrups can be said to be more rigid than the beam without external stirrups. Kesalahan desain awal, khususnya pemasangan sengkang, salah satunya dapat mengakibatkan balok mengalami kegagalan geser akibat kapasitas sengkang yang terpasang kurang dari kapasitas geser yang terjadi. Perkuatan geser pada penelitian ini menggunakan sengkang ∅6-75 yang dipasang pada daerah geser saja. Hasil dari perhitungan analisis, kapasitas geser dapat meningkat sampai 137,82%; 133,42% dan 137,12% sedangkan dari hasil pengujian mengalami peningkatan sebesar 31,58%; 0% dan 4,76% dalam hal ini peningkatan beban tidak terlihat sesignifikan dari hasil analisis perhitungan, namun jika dilihat dari pola retak yang terjadi beton tanpa perkuatan sengkang luar mengalami kombinasi retak lentur dan geser yang cukup banyak, selain kombinasi retak lentur dan geser, juga terjadi retak akibat balok tekan yang mencapai kapasitas tekan terlebih dahulu daripada balok tarik karena rasio tulangan yang terpasang over reinforced. Sementara itu pada balok dengan perkuatan sengkang luar, pola retak yang terjadi juga kombinasi retak lentur dan retak geser, namun retak yang terjadi relatif lebih sedikit daripada balok tanpa perkuatan. Jika ditinjau dari lendutan yang terjadi pada saat crack pertama, balok yang diberi perkuatan mengalami lendutan yang relatif lebih kecil yaitu 0,61 mm; 0,31 mm dan 0,18 mm daripada balok tanpa perkuatan 1,28 mm; 0,55 mm dan 0,32 mm sehingga balok yang diperkuat dengan sengkang luar dapat dikatakan lebih kaku daripada balok tanpa perkuatan.